2011
DOI: 10.1007/s11250-011-9963-5
|View full text |Cite
|
Sign up to set email alerts
|

First report of Neospora caninum infection in cattle in Sudan

Abstract: A cross-sectional survey was conducted in Sudan to determine sero-prevalence and risk factors associated with Neospora caninum infection in nonvaccinated dairy herds and to assess importance of the disease. Blood samples were collected from a total of 262 animals from 25 herds. Sera were tested for antibodies against N. caninum using ELISA test. The prevalence rates of N. caninum antibodies in cattle were high both at herd level (44%) and at individual animal level (10.7%). Herd level infection rates were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Neosporosis has been reported in many countries (Kim et al, 2002;Kim et al, 1998;Gondim et al, 2004) with different prevalence rates since the disease was recognized in 1988. The seroprevalence of antibody to N. caninum in this study is 4.84%, in dairy cattle of western dairy pocket area in Chitwan, is lower than that reported for cattle in Brazil (14.09%) (Gondim et al, 2004), Romania (34.6%) (Gvavrea et al, 2011), Pakistan (43%) (Nazir et al, 2013), Jordan (35 %) (Talafha and Al-Majali, 2013), China (15.07%) (Xu et al, 2012), India (12.61%) (Sengupta et al, 2012), Iran (10.5%) (Nematollahi et al, 2011), Sudan (10.7%) (Ibrahim et al, 2012) but resembles that reported in Australia (3.2%) (Nasir et al, 2012), Korea (4.1%) (Kim et al, 2002), Czech Republic (5.83%) (Vaclavek et al, 2003), France (5.6%) (Ould et al, 1999) and Japan (5.7%) (Koiwai et al, 2006). This difference in seroprevalence may be due to the type of test used, their cut-off points, change in geographic area, variation in sample size and other associated risk factors.…”
Section: Resultsmentioning
confidence: 69%
“…Neosporosis has been reported in many countries (Kim et al, 2002;Kim et al, 1998;Gondim et al, 2004) with different prevalence rates since the disease was recognized in 1988. The seroprevalence of antibody to N. caninum in this study is 4.84%, in dairy cattle of western dairy pocket area in Chitwan, is lower than that reported for cattle in Brazil (14.09%) (Gondim et al, 2004), Romania (34.6%) (Gvavrea et al, 2011), Pakistan (43%) (Nazir et al, 2013), Jordan (35 %) (Talafha and Al-Majali, 2013), China (15.07%) (Xu et al, 2012), India (12.61%) (Sengupta et al, 2012), Iran (10.5%) (Nematollahi et al, 2011), Sudan (10.7%) (Ibrahim et al, 2012) but resembles that reported in Australia (3.2%) (Nasir et al, 2012), Korea (4.1%) (Kim et al, 2002), Czech Republic (5.83%) (Vaclavek et al, 2003), France (5.6%) (Ould et al, 1999) and Japan (5.7%) (Koiwai et al, 2006). This difference in seroprevalence may be due to the type of test used, their cut-off points, change in geographic area, variation in sample size and other associated risk factors.…”
Section: Resultsmentioning
confidence: 69%
“…This indicates that other agents may be involved in these problems. Indeed, earlier studies have shown that agents such as bovine viral diarrhea virus, bovine herpes viruses 1 and 4, Akabane virus and Neospora caninum were highly prevalent in cattle in Sudan [25–27]. …”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmada, atık yapmış sığırların %32,35'inde N. caninum tespit edilmiştir. Çalışma sonucu, çeşitli ülkelerde atık yapan sığırlarda N. caninum yaygınlığının c-ELISA ile araştırıldığı çalışmalarla karşılaştırıldığında, Bulgaristan'dan (%10) [15], Çekya'dan (%0,5-3,9) [8,15], Polonya'dan (%15,6) [15], Slovakya (%22,2)'dan [15], Sırbistan'dan (%7,2-15,4) [22,23], Romaya'dan (%27,7) [20] ve Sudan'dan (%10,7) [18], daha yüksek bulunmuşken, yine bu oranın Brezilya'dan (%42,1), Meksika'dan (%42-59), ABD'den (%79), Portekiz'den (%49), İspanya'dan (%35,4), İsveç'ten (%63), Birleşik Krallık (%60), Yeni Zelenda (%50-53)'dan [15] ve Pakistan'dan (%43) [27] daha düşük olduğu görülmüştür.…”
Section: Tartışma Ve Sonuçunclassified